ISTEM PENUNJANG KEPUTUSAN PENGUKURAN KINERJA KARYAWAN MENGGUNAKAN METODE ANALYSIS HIERARCHY PROSES PADA PT. NSC FINANCE MARISA - Jorry Karim (Teknosains, 2016)
Measurement of the performance of a company is very importantto evaluate and plan for the future. Absolute performance appraisal shouldbe done to determine the performance of each employee to be achieved. Forthat each company has a different way of assessing employee performance.In practice, the assessment of the performance of the employees should bedone with a good and appropriate methods, so there is no error in judgment.The results of the assessment should be done to ensure a fair andsatisfactory treatment for employees who are assessed, so that in turn fosterloyalty and morale. There are several tools that are commonly used formeasuring the performance of employees, namely Decision Support SystemAnalysis method Hierarchy Process (AHP). Decision support system is atool that can be used to assess employee performance by comparing criteriaand alternatives employees. This research was built using the MySQLdatabase, and using Dreamweaver for web development, and PHPprogramming language.